Observation of Aulter–Townes splitting in subwavelength grating metamaterial ring resonators - Wanxin Li; Jiewen Li; Lin Yu; Yang Feng; Yong Yao; Yunxu Sun; Yi Zou; Xiaochuan Xu (APL Photonics, 2023)
Subwavelength grating metamaterial (SGM) waveguide is typically treated as a homogeneous medium without considering intra-waveguide reflection. However, this approximation is not always valid, especially in resonators. In this paper, we show that the reflection-induced mutual coupling between the clock-wise and counter-clock-wise resonant modes in a subwavelength grating metamaterial waveguide ring resonator (SGMRR) breaks the degeneracy of the two modes, leading to the formation of Autler–Townes splitting. This phenomenon could be leveraged to improve the detection limit of SGMRR-based sensors.